Association Between Education Level and Household Income and Period Poverty Among Women of Reproductive Age in Klampok Village, Singosari District, Malang Regency - Firdaus, Annisa' Nurul; Fransiska, Ratna Diana; Kurnianingsih, Nia (TRI DHARMA MANDIRI: Dissemination and Downstreaming of Research to the Community (Journal of Community Engagement), 2025)
Period poverty refers to limited access to menstrual products, adequate sanitation facilities, and menstrual health education, all of which are essential for reproductive health among women of reproductive age (WRA). However, data on the prevalence and risk factors of period poverty remain limited, particularly in Malang Regency. This study aimed to identify the level of period poverty and to analyze its association with education level and household income among WRA in Klampok Village, Singosari District, Malang Regency. This cross-sectional study involved 62 WRA selected through accidental sampling. Data were collected using a structured questionnaire covering sociodemographic characteristics, education level, household income, and a modified version of the Menstrual Practice Need Scale (MPNS-36). The findings indicated that 53.23% of respondents experienced low levels of period poverty, while 46.77% experienced moderate levels. Education level was not significantly associated with period poverty (p = 0.922), nor was household income (p = 0.488). These results suggest that education level and household income are not associated with period poverty among WRA in Klampok Village, Singosari District, Malang Regency. Future large-scale studies are needed to identify other risk factors associated with period poverty within broader population characteristics.